How farmers understand their autonomy and the significance of this understanding for environmental management in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Environmental Management at Massey University, New Zealand - McCole, Hannah (Massey University, 2022)
This thesis explores farmer understanding of autonomy and what this means for environmental management. Whilst prior research has shown that farmers place a high value on their autonomy, there has been little work conducted to understand how significant maintaining this autonomy is for environmental management. In New Zealand, ongoing conflict regarding top-down agricultural regulation and the current momentum towards establishing farmer-led catchment collectives suggests that farmers want to maintain autonomy over the environmental action that they take. To explore farmer understandings of autonomy in the context of environmental management, this research undertook semi-structured interviews with nine dairy farmers in the Waikato region utilizing a thematic analysis approach. The key findings revealed that farmer autonomy is complex, it is not static. This research also identified four recurring components of autonomy which were embedded within the interviewees’ collective understanding of their autonomy. These components indicated that farmers often defined their autonomy as their ability to 1) act as active sharers rather than passive receivers of knowledge, 2) use modes of self-regulation via collective action, 3) pursue their interests and values without fear of undue financial constraints, and 4) enact their own sense of obligation to their land in accordance with their personal stewardship values. Overall, this research supports the idea that farmer autonomy can be preserved whilst achieving beneficial environmental outcomes through the promotion of farmer-led collaborative groups and networks that encourage farmer knowledge exchange. This study also highlights the importance of creating mechanisms that provide farmers with financial support and acknowledge farmer feelings of responsibility for their land. This research therefore argues that a top-down regulatory approach which inadvertently marginalises farmer autonomy may be detrimental to the future of effective environmental management in New Zealand.
Keywords: 410404 Environmental management